Functional magnetic resonance imaging of real and sham acupuncture. - Parrish, T.B (IEEE Engineering in medicine and biology magazine)
Functional magnetic resonance imaging (fMRI) is an ideal method to noninvasively explore the whole brain for cortical activation related to acupuncture. The results from this study demonstrate that fMRI can identify specific cortical regions associated with acupuncture stimulation. The choice of acupuncture stimulation using visual or auditory points simplifies the interpretation of the results because the anatomic correlates are well defined. The magnitude and extent of the activations were different for the auditory and the visual stimulation; this may be due to the relative potency of the acupuncture points used, the overall imbalance associated with these systems, and the interpretation of the acupuncture point by the acupuncturist. Nevertheless, these data reflect significant blood-flow changes within the appropriate regions of the brain in response to stimulation of acupuncture points in the lower leg. With the appropriate experimental design, a clearer understanding of the neural substrate associated with acupuncture is likely to provide considerable insights into acupuncture treatment. This type of scientific approach to investigating and validating alternative medicine techniques is critical for the widespread acceptance of these methods.